Immunological and microbiological features of the mucous membranes of the oronasopharyngeal region of patients with postcovid syndrome - A. R. Marzhokhova; Z. F. Kharaeva; M. Yu. Marzhokhova; Z. A. Shomakhova (Лечащий Врач)
Background. One of the most frequent complaints of patients who have undergone COVID-19 are various purulent-inflammatory diseases of the organs of the oronasopharyngeal region of a recurrent nature, in connection with which it is relevant to investigate the causes of the failure of the protective potential of the upper respiratory tract, mucous membranes of this area. The aim of the study was to study the immunological and microbiological features of the mucous membranes of the oronazopharyngeal region in patients with postcovid syndrome who had suffered a severe form of COVID-19 and had complaints from the organs of the oronazopharyngeal region.Materials and methods. Patients who suffered a severe form of new coronavirus infection (NCI) from 3 to 6 months ago were examined. Concentrations of local interleukins 1ß, interleukin-10, sIgA, facultative anaerobic microflora of mucous membranes of the oronazopharyngeal region were studied.Results. The data obtained indicate that patients who have suffered a severe form of new coronavirus infection 3-6 months after discharge from the hospital have complaints of impaired sense of smell, taste, dysphonia, tinnitus. In the study of facultative anaerobic microflora of the nose and pharynx of patients with postcovid syndrome, data on the frequency of detection of strains of Staphylococcus aureus, Klebsiella pneumoniae and yeast-like fungi Candida albicans are noteworthy, regardless of the presence of acute stage diseases at the time of examination, unlike patients with rhinosinusitis or pharyngitis who have not undergone NCI. When assessing the concentration of sIgA in saliva and in the pharyngeal scraping material and local concentrations of IL-1β, it was found that in groups of patients with postcovid syndrome, the level of sIgA and IL-1β, regardless of the presence or absence of acute forms of bacterial infections, did not significantly differ from the norm (p > 0.05). That is, in response to the presence of pathogenic and conditionally pathogenic bacteria and their activation, an increase in the humoral immunity of the mucous membranes and activation of cytokine-mediated mucosal protection reactions were not detected, which is evidence of a local immunodeficiency condition.